2007
DOI: 10.1038/sj.leu.2404607
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase expression in B-cell chronic lymphocytic leukemia predicts survival and delineates subgroups of patients with the same igVH mutation status and different outcome

Abstract: Activation of telomerase reverse transcriptase (hTERT) is essential for unlimited cell growth and plays a critical role in tumorigenesis. We investigated hTERT gene expression in 134 B-cell chronic lymphocytic leukemia (B-CLL) cases and evaluated its prognostic value with other prognostic markers (IgVH mutation status, CD38 and ZAP-70 expression). Real-time PCR assays to quantify either all hTERT transcripts (AT) or only the full length (FL) transcript encoding the functional protein were developed. hTERT-AT l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 39 publications
4
54
1
1
Order By: Relevance
“…un-mutated IGHV with long telomere and mutated IGHV with short telomeres (Ricca et al, 2007). It seems possible therefore that TL analysis could be used to risk stratify CLL patients, resulting in patients who are low risk being spared unnecessary treatment (Terrin et al, 2007). This study also highlighted another consideration for TL as a useful marker in clinical practice for patient prognosis.…”
Section: Chronic Lymphocytic Leukaemiamentioning
confidence: 77%
“…un-mutated IGHV with long telomere and mutated IGHV with short telomeres (Ricca et al, 2007). It seems possible therefore that TL analysis could be used to risk stratify CLL patients, resulting in patients who are low risk being spared unnecessary treatment (Terrin et al, 2007). This study also highlighted another consideration for TL as a useful marker in clinical practice for patient prognosis.…”
Section: Chronic Lymphocytic Leukaemiamentioning
confidence: 77%
“…The quantification of all hTERT transcripts (hTERT-AT) in CRC samples was carried out by real-time PCR, exactly as previously described (Terrin et al, 2007(Terrin et al, , 2008, and normalised for 10 3 copies of the housekeeping hypoxanthine guanine phosphoribosyl transferase 1 (HPRT1) gene (Terrin et al, 2008).…”
Section: Quantification Of Htert Transcriptsmentioning
confidence: 99%
“…A number of reports have shown that short telomeres and expression of h-tert, the catalytic subunit of telomerase, are poor prognostic factors in this neoplasm. [24][25][26][27] Although early studies postulated that telomere length (TL) was mostly acting as a surrogate marker for IGHV-MS, a number of subsequent reports indicated that in discordant cases TL performed better than IGHV-MS, suggesting that TL deserved further consideration as a prognostic biomarker in CLL. 28,29 Despite these encouraging results, additional experience needs to be accumulated on TL as a prognostic marker in CLL.…”
Section: Introductionmentioning
confidence: 99%